2002
DOI: 10.1038/sj.bjc.6600254
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of active specific immunotherapy and5-FU/Leucovorin as adjuvant therapy for stage III colon carcinoma

Abstract: Active specific immunotherapy, using vaccines with autologous tumour cells and BCG, significantly reduces the rate of tumour recurrence in stage II colon cancer patients, while no clinical benefit has yet been observed in stage III patients. Adjuvant treatment with 5-Fluorouracil/Leucovorin is now considered standard therapy for stage III colon carcinoma and results in an absolute survival benefit of approximately 10%. Yet, the 5-year overall survival rate of stage III colon cancer patients is only 40 -50%. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Therapeutic vaccination with specific tumor antigens was attempted in many clinical trials, resulting in partial response in some of the treated patients, while a complete tumor regression was observed in only a small fraction of the patients. It was suggested that the preferred time for immunotherapy is at the minimal residual disease stage, because micro-metastases are expected to be more responsive than large tumors with their immune suppressing microenvironment (21,22, reviewed in Ref. 23).…”
Section: Tumor Immunologymentioning
confidence: 99%
“…Therapeutic vaccination with specific tumor antigens was attempted in many clinical trials, resulting in partial response in some of the treated patients, while a complete tumor regression was observed in only a small fraction of the patients. It was suggested that the preferred time for immunotherapy is at the minimal residual disease stage, because micro-metastases are expected to be more responsive than large tumors with their immune suppressing microenvironment (21,22, reviewed in Ref. 23).…”
Section: Tumor Immunologymentioning
confidence: 99%
“…Recently, active specific immunotherapy (ASI) consisting of autologous tumor cells mixed with BCG (OncoVAX) administered through intradermal vaccinations has become a treatment option for stage II colon cancer patients in an adjuvant setting 26–28 . Combining chemotherapy and immunotherapy might improve prognosis for stage III colon cancer patients, especially if ASI and chemotherapy, mainly 5‐FU + LV, truly show synergistic effects on each other 29 …”
Section: Discussionmentioning
confidence: 99%
“…Vaccine preparations based on autologous tumor tissue frequently consist of autologous single tumor cell suspensions, obtained from tumor tissue. Before reinjection, the tumor cells are irradiated and usually combined with immune-stimulating agents: heat shock proteins [78], Ulster strain of the Newcastle disease virus (NDV) [25,79,80], BCG [81][82][83][84][85] and IL-2-transfected fibroblasts [86].…”
Section: Strategies Of Cell-derived Vaccinationmentioning
confidence: 99%
“…Six out of the eight clinical Phase II [25,80,83] and Phase III [80][81][82][83][84][85] studies, determined the effect on prognosis and specifically, three studies reported that tumor cell reinjection combined with BCG had an effect on survival in two subgroups: stage II patients [81,82] and patients with colon cancer [85]. Furthermore, one randomized Phase III trial (where NDV-infected autologous tumor cells were injected) reported a significant effect on survival when compared with non vaccinated patients [80].…”
Section: Strategies Of Cell-derived Vaccinationmentioning
confidence: 99%